Historical Review of Learning Strategies Research: Strategies for the Whole Learner—A Tribute to Claire Ellen Weinstein and Early Researchers of This Topic - McCombs, Barbara L. (Frontiers in Education, 2017)
This selective historical review summarizes research on learning strategies conducted in the past 50 years and summarizes how the field has evolved. Two goals guide the review: (1) update the literature on the origins of the learning strategies research ‘movement’ and (2) highlight in the supplement the work of one of the early contributors, Claire Ellen Weinstein, whose pioneering work endures up to now. This review fills the gap of other recent reviews by including research on learning strategies began in the 1960s and 1970s that received significant funding from military sources but remained largely hidden in technical reports and hard to find academic documents. The outcomes of this review reveal that the field is thriving, with two major unifying themes. First, there is a focus on metacognition and second, there is a focus on the whole learner and interventions that address cognitive, metacognitive, affective, physical, cultural, and social needs. The research of Dr. Weinstein (who passed June 23, 2016) has framed past and current learning strategies research agendas and includes her development, validation, and implementation of the Learning and Study Strategies Inventory (LASSI) in traditional and online learning contexts. This review and supplemental section’s personal stories include many of the early learning strategies research findings, definitions, and interventions that remain in use across the nation and world today. Future research issues and areas needing more focused attention in the years ahead given our increasing complex, digital, and diverse world are summarized in final sections of this review.